Species asynchrony and response diversity determine multifunctional stability of natural grasslands. (5th March 2019) - Sasaki, Takehiro; Lu, Xiaoming; Hirota, Mitsuru; Bai, Yongfei
Abstract: A growing body of empirical evidence has suggested that biodiversity affects the simultaneous performance of multiple ecosystem functions (i.e. ecosystem multifunctionality). Given increasing environmental variability and uncertainty under global change, an emerging question is how biodiversity influences the stability of multiple functions (i.e. multifunctional stability). We currently know little, however, about the determinants and mechanisms of multifunctional stability, which is of practical importance for ensuring the sustainable provision of multiple functions. Here, we examined mechanisms contributing to stability (quantified as the ratio of the mean to the standard deviation) of multiple functions related to ecosystem productivity and carbon sequestration, including plant above‐ground and below‐ground productivity, litter production, gross primary productivity and ecosystem respiration, in a large grassland biodiversity experiment in Inner Mongolia. We found that community‐wide species asynchrony was a strong driver to stabilize multiple functions. Community‐wide asynchrony mediated the positive effects of species richness and response diversity (describing how species with similar effects on ecosystem function respond differently to environmental change) on multifunctional stability. However, species richness had a negative direct effect on multifunctional stability because, although it increased the averaged temporal mean of multiple functions, it strongly increased the averaged temporal standard deviation of multiple functions. The overall effects of species richness on multifunctional stability were thus negative, whereas those of response diversity were positive. Synthesis . The studied ecosystem functions related to ecosystem productivity and carbon sequestration are important in natural grasslands across the world. We conclude that species asynchrony and response diversity, rather than species richness, are key to the ecosystem multifunctional stability. The loss of response diversity and compensatory mechanisms would likely reduce the long‐term sustainability of grasslands in the face of global change. Abstract : We demonstrated that community‐wide species asynchrony and response diversity, rather than species richness, are key to the ecosystem multifunctional stability. The studied ecosystem functions related to ecosystem productivity and carbon sequestration are important in natural grasslands across the world. The loss of response diversity and compensatory mechanisms would likely reduce the long‐term sustainability of grasslands in the face of global change.